The Biodegradable Food Packaging with The Addition of ZnO Nanoparticles - Annisa Rizky Salsabila; Asep Bayu Dani Nandiyanto (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Zinc oxide nanoparticle properties that can improve the quality of biodegradable food packaging become the impetus to develop research on biodegradable food packaging with the addition of ZnO nanoparticles. However, it is not yet known whether research on this topic is still widely carried out or not. This study aims to know the development of this research topic from 2013 to 2022 through a bibliometric approach with computational mapping analysis using VOSviewer. The search for article data from Google Scholar database was carried out by entering a query language into Publish or Perish. There are 207 articles that meet the criteria after being filtered by reading the title and abstract. Based on the number of publications each year, research on this topic is relatively increasing. Based on three mapping visualizations from VOSviewer results, the relation of packaging to properties or capabilities, such as biodegradability, extending the food shelf life, and antimicrobial activity is still rarely discussed. These results can be a reference for researchers to develop research on biodegradable food packaging with the addition of ZnO nanoparticles, with a discussion focusing on these properties or capabilities.